Agricultural Research in Himachal Pradesh: A Profile Based on Agricola, Agris, CAB and FSTA CD-ROM Databases - Hasan, Nabi; Singh, Sewa (Journal of Information and Knowledge, 2007)
Presents an assessment of contributions on Himachal Pradesh to agriculture and allied fields based on publications indexed in AGRICOLA, AGRIS, CAB Abstracts and FSTA CD-ROM databases during 1990-1994. Attempts to provide detailed analysis of 2,451 contributions on Himachal Pradesh covered by the databases of the study period. This macroscopic study tries to answer questions such as which institutions are carrying out the research, in which journals, contributions on Himachal Pradesh get published, in what sub-fields the contributors are strong, and so on. The paper maps the field under the following heads; quantum of production, form-wise distribution, authorship pattern, institutions, ranking of periodicals, subject dispersion, citation study, length of publications, languages of publications, languages of summaries, country-wise productivity, state-wise productivity and classification by journal impact factor.